Students’ Negative Attitudes toward Learning EFL Module within Specialties at Algerian University - AHMED, Mohammed Amin (My University, 2018)
Attitudes in Foreign Language Teaching greatly influence the learner’s outcome in class. The present research work is conducted at investigating the students’ negative attitudes toward leaning English as a Foreign Language (EFL) module within specialties at Algerian university. The focus of the study is put on the reasons why the majority of students are not interested in learning English as a module within their specialties. The study aims to discover the main causes behind the lack of interest of students toward their English tutorial, and also to identify the major factors that could influence their attitudes negatively. In that sense, the study hypothesizes that the majority of students believe that they do not need English in their future jobsand the dominance of French language as the language of higher educational system of most specialties at Algerian university influences the students’ attitudes toward learning English. In order to reach the set up objectives and aims, the research is conducted quantitatively and qualitatively. In the sense that this study employs two different tools: a questionnaire and an interview
The Case Study of Mostaganem University ( Abdelhamid Ibn Badis)
Keywords: Attitudes; EFL module; Negative views; ESP